Non-invasive high-frequency oscillatory ventilation in preterm infants: a randomised controlled cross-over trial. Issue 4 (16th September 2017) - Klotz, Daniel; Schneider, Hendryk; Schumann, Stefan; Mayer, Benjamin; Fuchs, Hans
Abstract : Objective: Non-invasive high-frequency oscillatory ventilation (nHFOV) has recently been described as a novel mode of respiratory support for premature infants. This study was designed to determine whether nHFOV decreases CO2 partial pressure (pCO2 ) in premature infants more effectively than non-invasive continuous positive airway pressure (nCPAP). Design: Non-blinded prospective randomised controlled cross-over study. Setting: University Medical Center tertiary neonatal intensive care unit. Patients: 26 premature infants of 27±2 weeks of gestational age after extubation or non-invasive surfactant treatment. Interventions: Infants were treated with 4 hours of nHFOV and 4 hours of nCPAP in a cross-over design. The sequence of the ventilation mode was randomly allocated. Main outcome measures: The primary outcome measure was pCO2 of arterial or arterialised blood 4 hours after commencing the respective mode of respiratory support. Secondary outcome criteria included events of apnoea and bradycardia, respiratory rate, heart rate, pain and/or discomfort, mean airway pressure, fraction of inspired oxygen and failure of non-invasive respiratory support. Results: pCO2 after 4 hours of nHFOV was similar compared with 4 hours of nCPAP (p=0.33). pCO2 was 54.8 (14.6) vs 52.7 (9.3) mm Hg mean (SD) for the nHFOV–nCPAP period (n=13) and 49.0 (8.1) vs 47.7 (9.5) mm Hg for the nCPAP–nHFOV period (n=13). There was no difference in any of the secondary outcome measures. nHFOV was terminated prematurely in five cases for predefined failure criteria (p=0.051). Conclusions: We could not demonstrate an increased carbon dioxide clearance applying nHFOV compared with nCPAP in this cohort of preterm infants. Trial registration number: DRKS00007171, results.